Peningkatan Efisiensi Pemesinan Mesin Cnc Training Unit (Tu) 2 – Axis Unimat Uni Dreh Estop Melalui Integrasi Software Cad/Cam - Kamarullah; Taufan Arif Adlie; Suheri; Syamsul Bahri Widodo (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
This study aims to enhance machining efficiency on the CNC Training Unit (TU) 2-Axis Unimat Uni Dreh Estop machine by integrating CAD/CAM software using Mastercam 2020. The research methods included creating 2D and 3D designs, generating toolpaths, simulating tool feed movements, converting designs into G-Code, and conducting tests on a 2-Axis CNC Turning machine. The workpiece material used was an aluminium blank measuring Ø12 × 100 mm. The results showed that the use of Mastercam significantly improved the efficiency of CNC program creation compared to the manual method. The total machining process time was reduced from 43.02 minutes to 28.02 minutes. In addition, the simulation feature in Mastercam was able to minimize programming and operational errors before the machining process was carried out. The machining results also demonstrated a level of precision consistent with the designed specifications. Therefore, the integration of CAD/CAM software into the CNC Turning 2-Axis TU Unimat Uni Dreh Estop machine can enhance the effectiveness and efficiency of the machining process while reducing the risk of errors in the production process.